Impact of a clinical pharmacist in an outpatient heart transplant clinic. Issue 12 (8th October 2021) - Prom, Alyson; Ricciuti, Domenica; Walter, Krysta; Newman, Jessica; Doligalski, Christina
Abstract: Introduction: Pharmacotherapy‐related prevention of cardiac allograft vasculopathy, optimal immunosuppression regimens, and metabolic management are essential for promotion of graft survival in heart transplant recipients. Methods: Following the addition of an ambulatory clinical pharmacist to the heart transplant team at an academic medical center in January 2018, we sought to assess the impact of pharmacist integration on pharmacotherapy‐related clinical outcomes including goal blood pressure, diabetes control, appropriate statin and aspirin utilization, tacrolimus variability, and patient and graft outcomes at 1 year postheart transplant via a retrospective pre‐post analysis. Results: Fifty‐nine heart transplant recipients were included. At 1 year, the pharmacist cohort had a higher percentage of heart transplant recipients at goal blood pressure (93.1 vs 71.4%, P = .03), on a statin (96.7 vs 67.9%, P = .004), and with fewer 1 year hospital readmissions (55 vs 28, P = .03); no significant differences in HbA1c, aspirin use, tacrolimus level variability, or patient and graft survival were observed. Discussion: This analysis suggests that the integration of a pharmacist into the routine ambulatory care of heart transplant recipients is associated with improvement in several pharmacotherapy‐related clinical outcomes.